Corporate Attributes and Earnings Management: Evidence from Listed Non-Financial Firms in Nigeria - Odokwo , Rose Augustine; Ibok, Nkanikpo; Ukpong, Eno Gregory (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
The financial reporting practices of firms are usually influenced the certain attributes specific to such firms. The main objective of this study therefore, was to examine the effect of corporate attributes on earnings management practices of nonfinancial firms listed on the Nigerian Exchange Group for the period 2014 to 2023. The research design adopted for this study was ex post facto. Secondary data were used and the population of the study was 109 listed nonfinancial. Purposive sampling technique was adopted to select 70 companies as the sample size of this study. The Robust regression technique was used in analyzing the data and the statistical software employed was STATA 16. The results of the analysis revealed that firm age has significant negative effect on real earnings management; firm size has significant negative effect on real earnings management; and profitability has significant negative effect real earnings management of listed nonfinancial firms in Nigeria. Based on these findings, it was thus concluded that corporate attributes significantly influence earnings management practices of listed nonfinancial firms in Nigeria. It was therefore recommended among others Government and regulatory bodies should provide additional support and guidance to smaller firms to help them establish strong financial controls and reduce the possibility of earnings management.